A multicentre qualitative study assessing implementation of an Enhanced Recovery After Surgery program. Issue 6 (December 2018) - Martin, D.; Roulin, D.; Grass, F.; Addor, V.; Ljungqvist, O.; Demartines, N.; Hübner, M.
Summary: Background & aims: The existence of enhanced recovery specific guidelines (ERAS) is not enough to change patient management practice since many barriers exist to successful ERAS implementation. The present survey aimed to analyse motivations for implementation as well as encountered difficulties and challenges. Further, relevance and importance of perioperative care items and postoperative recovery targets were assessed. Methods: A multicentre qualitative study was conducted between August and December 2016 among surgeons, anaesthesiologists and nurses from implemented ERAS centres in Switzerland (n = 16) and Sweden (n = 14). An online survey (31 closed questions) was sent by email, with reminders at 4, 8 and 12 weeks. Results: Seventy-seven out of 146 experts completed the survey (response rate 52.7%). Main motivations to implement ERAS were the expectation to reduce complications (91%), higher patient satisfaction (73%) and shorter hospital stay (62%). The application of ERAS program represented major changes in clinical practice for 57% of participants without significant differences between various specialities (surgeons: 63%, nurses: 63%, anaesthesiologists: 36%, p = 0.185). The most important barriers for straightforward implementation were time restraints (69%), opposing colleagues (68%) and logistical reasons (66%). The 3 most frequently cited patient-related barriers to adopt ERAS were opposing personality (52%), co-morbidities (49%) and language barriers (31%). Conclusions: Implementing ERAS care into practice was challenging and required important changes in clinical practice for all involved specialities. Main reasons for implementation were the expectation to reduce complications and hospital stay with improved patients' satisfaction. Main barriers were time restraints, reluctance to change and logistics.